2012
DOI: 10.1038/ejhg.2012.13
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of genetic health professionals' experience with direct-to-consumer genetic testing in their clinical practice

Abstract: Direct-to-consumer genetic testing (DTC-GT) allows individuals to obtain genetic tests directly from companies without necessarily involving health professionals. This study explores genetic health professionals' opinions of health-related DTC-GT and the reported frequency of individuals presenting to clinical genetics services after undertaking testing. Genetic counsellors and clinical geneticists, members of the Human Genetics Society of Australasia, completed an online survey in mid 2011. The 130 genetic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 27 publications
5
57
1
2
Order By: Relevance
“…In addition, there are issues for equity of access to health information, when private provision is determined by ability to pay, and for the potential for public confidence in genetic testing more generally to be undermined by controversy about DTC services. 28 While one recent study 29 found that DTC genetic testing is not yet a major reason for referral for follow-up with clinical genetic services in Australia and New Zealand, analysis from the United States 30 indicates that a relatively high proportion of subjects using DTC genetic testing services discussed the results with their own physician-and this has resource implications.…”
Section: Understanding and Addressing Consequences For Health Systemsmentioning
confidence: 99%
“…In addition, there are issues for equity of access to health information, when private provision is determined by ability to pay, and for the potential for public confidence in genetic testing more generally to be undermined by controversy about DTC services. 28 While one recent study 29 found that DTC genetic testing is not yet a major reason for referral for follow-up with clinical genetic services in Australia and New Zealand, analysis from the United States 30 indicates that a relatively high proportion of subjects using DTC genetic testing services discussed the results with their own physician-and this has resource implications.…”
Section: Understanding and Addressing Consequences For Health Systemsmentioning
confidence: 99%
“…Some argue that science is in its infancy and that results are not valid or accurate enough to warrant mass marketing of the tests (American College of Medicine Genetics Board of Directors 2004; Committee on Genetics, American College of Obstetricians and Gynecologists 2008;Federal Trade Commission 2006;Hudson et al 2007). Others' concerns lie with the potential burden these tests could have on the limited resources of the medical system (Brett et al 2012;Burke 2008, 2011;White et al 1999). If consumers used these tests and received unfavorable results, they might overwhelm their physicians' offices requesting help with understanding and interpreting DTCGT results and/or additional testing or screenings for conditions for which they may or may not be at high risk (Giovanni et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[14-16] Hock et al . gathered data in 2008 on the knowledge and beliefs of 312 American genetic counsellors, almost half of whom had at least one patient initiate a discussion on DTC GT in the last 2 years and 14% had been asked to discuss or interpret DTC genetic test results[16].…”
Section: Introductionmentioning
confidence: 99%
“…These 22 providers who performed a DTC GT consultation represent 16.5% of the 133 providers who completed the study questionnaire [15]. Brett et al [14] recently reported on the experiences of 130 genetic counsellors and 38 clinical geneticists (members of the Human Genetics Society of Australasia); they focused primarily on the description of 25 clients who had consulted 19 healthcare professionals regarding DTC GT. Six empirical articles focusing primarily on physicians' views of, and/or experiences with DTC GT have been published to date.…”
Section: Introductionmentioning
confidence: 99%